GERAKAN TERTIB LALU LINTAS âGETASâ: UPAYA PENCEGAHAN KECELAKAAN SEJAK DINI - Pratiwi, Restu Dyah Siam; Irvani, Achsanul Fahruddin; Nastiti, Wahyu Kurnia Dewi; Rohmah, Itsna Amanatur (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2014)
Surabaya has the largest traffic accident than others in east java (Surabaya Kompas, 2013). There is not any attention and awareness from students of junior high school to prevent accident increasing. Therefore, it needing oncoming to get studentâs attention for developing their concern about traffic rules. One of this effort is making âGETASâ (Gerakan Tertib Lalu Lintas) community. This is a traffic discipline community that involve the students of Yapita Junior High School Surabaya as the first members. They have a big duty toÂ  prove their awareness about traffic, so they can add another friend to join their community. The method that used in this program is âinnovationâ game. Â This system aims to createÂ  softskilled andÂ  responsive student. Â By means of game, the student can give their more attentionÂ  so the substance can delivered easily. The result can be identified by assessment about knowing and care. Â Knowing is assessed by pre test and post test. Base on this test, there is inceasing knowledge from 67,2% to 90,6%. Whereas another result is assessed from studentâs enthusiastic to creat âGETASâ community. This program is expected to decreas traffic accident in Surabaya and others.Â Keywords : âGETASâ community, knowing, care